HUBUNGAN KEBIASAAN MEROKOK ANGGOTA KELUARGA DI DALAM RUMAH DENGAN ISPA PADA BALITA DI DESA LAUT TADOR, KABUPATEN BATUBARA - ASNITA YANI MAJRUL; BALQIS NURMAULI; DEALITA KHAIRANI DAULAY (JURNAL ILMIAH MAKSITEK, 2022)
This study aims to determine the relationship between smoking habits in the home by family members and the incidence of Acute Respiratory Infections (ARI) in toddlers in Laut Tador Village, Batubara Regency. This type of research is an analytic survey with a cross-sectional design. The population in this study were toddlers aged 0 months to 5 years with a total of 370 toddlers, 50 samples were taken using the purposive sampling technique. Data were analyzed univariately and bivariate with Fisher's Exact test. The parameter of the strength of the relationship with the Prevalence Ratio (RP). Most of the respondents had a habit of smoking in their family, namely 32 (64%) of respondents with toddlers who were exposed to ARI, namely 39 (78%) of respondents. It was found that there was a significant relationship between smoking habits in the house and acute respiratory infections in toddlers in Laut Tador Village, Batubara Regency with a probability of 0.001. The risk of experiencing ARI in toddlers who live in a house with smoking habits in the house is 1.875 times compared to a house where there is no smoking habit.